Manajemen Pre-Hospital pada Cardiac Arrest - Fatimah, Nurul; Tahir, Akina Maulidhany; Apris, Muh Asrul (Universitas Pahlawan Tuanku Tambusai, 2025)
Cardiac arrest is one of the main causes of death outside the hospital. The main cause of death that is most commonly found in developed or developing countries to date is in the form of cardiac arrest cases. Cases of cardiac arrest can result in death if not properly handled by medical personnel. Globally, the prevalence of cardiac arrest cases is quite high. This literature aims to find out the pre-hospital management of cardiac arrest. The method used is in the form of a literature review with a Narrative Review design. The results obtained in this literature are 10 articles obtained with limitations from 2020 – 2024. From this article, an in-depth analysis has been carried out that has the strengths and limitations of each article regarding pre-hospital management in cardiac arrest. From 10 articles, there was a significant relationship between pre-hospital management of cardiac arrest and the occurrence of ROSC. Some pre-hospital management in cardiac arrest that can be carried out are airway management, cardiopulmonary resuscitation (CPR), defibrillation, and emergency response system (EMS) activation. This literature concludes that it is important to immediately provide basic pre-hospital life support so that patients can be saved.